How Do We Get From Good to Great? The Need for Better Observation Studies of Creativity in Education - Katz-Buonincontro, Jen; Anderson, Ross C. (Frontiers in Psychology, 2018)
Without quality research using observation methods, it is difficult to understand creativity processes in action, especially in the field of education. But, what is the current state of these studies? Based on a review of 37 extant studies, we found that observation is surprisingly under-utilized, and that more rigorous observation studies of creativity processes in education are needed.